DNA Flow Cytometry Analysis in Body Cavity Fluids Using Liquid‐Based Cytology - Ryu, Ayumi; Honma, Keiichiro; Tsuzaki, Sayoko; Yoshioka, Risa; Tanada, Satoshi; Yamamoto, Takashi; Satomi, Hidetoshi; Nagata, Shigenori; Yamasaki, Tomoyuki; Ohue, Masayuki (Diagnostic cytopathology, 2025)
ABSTRACT Background DNA flow cytometry using LC‐1000 is utilized for analyzing cellular and nuclear lengths and DNA content in individual cells with samples in cell preservation solutions to acquire the cell proliferation index (CPIx). This study aimed to evaluate the performance of body cavity fluid cytology using LC‐1000. As cell preservation solutions, liquid‐based cytology (LBC) by Cellprep (CP) was compared with CelVerse (CeV), specifically designed for the LC‐1000. Methods Overall, we evaluated 43 samples (20 malignant and 23 benign) of body cavity fluids suspended in CeV and 59 samples (28 malignant and 31 benign) suspended in CP. The CPIx was compared between malignant and benign cases of CeV and CP. Further, the subject groups were divided according to the SubG1% in a sample. Results The CPIx in CeV was 0.14–10.22 (median 0.62) in malignant cases and 0.09–4.64 (median 0.19) in benign cases (p < 0.001); additionally, CP displayed 0.14–9.87 (median 0.84) in malignant cases and 0.11–3.02 (median 0.22) in benign cases (p < 0.001). The area under the curve (AUC) was 0.811 for CeV and 0.776 for CP. The difference in SubG1% between the CeV and CP groups was statistically significant (p < 0.0001) and influenced the AUC in CP. Conclusion The CPIx in CeV or CP samples using the LC‐1000 may be applicable as an objective indicator in body cavity fluid cytology. Samples preserved in CeV provided more consistent results, unaffected by SubG1%, when compared to those stored in CP.